Coronary Artery disease prevalence in patients having essential hypertension with Or without diabetes Mellitus detected by Cardiac MIBI scan - Owais Bin Qadeer Gill; Talal Abdul Rehman; Muhammed Shahzad Afzal; Hafiz Amjad Hussain (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: The aim of this retrospective study was to find the prevalence of coronary artery disease (CAD) in hypertensive patients with or without diabetes mellitus.METHODOLOGY: Data of patients having essential hypertension (n=931) referred to PINUM from April 2017 to December 2018 for stress/rest cardiac MIBI scan was analyzed. This data was divided into two groups. HD group contains data of patients having hypertension with diabetes mellitus (n=456, 48.98% of total population, M:F=245:211). While data of patients having hypertension without diabetes mellitus was placed in H group (n=475, 51.02% of total population, M: F=254:221).RESULTS: Prevalence of CAD is higher in HD group than in H group (47.8% vs. 30.1%; p<0.001). CAD is more prevalent in males than females in both groups (53.9 % vs. 40.8% in HD group, and 39.4% vs. 19.5% in H group). This difference in prevalence of CAD in HD and H groups is more marked in females (40.8% vs. 19.5%; p<0.001) than males (53.9 % vs. 39.4%; p=0.001). Prevalence of CAD in patients with typical presentation is not statistically significant in HD and H groups (72.3% vs. 68.4%; p=0.645), while in subjects with atypical presentation prevalence is significantly higher in HD group than H group (40.8% vs. 26.8%; p<0.001).CONCLUSION: Prevalence of CAD is higher in the group of patients having essential hypertension with diabetes mellitus than the group of patients having essential hypertension without diabetes mellitus.